Home Forums Algebra Sequence and Series

Viewing 1 post (of 1 total)
  • Author
    Posts
  • #24346
    admin
    Keymaster

    The sum of the series $- \frac{2}{3} + \frac{2}{9^2} + \frac{10}{9^3} + \frac{18}{9^4} + \frac{26}{9^5} + \cdots \infty $ is sought. To find this sum, we observe that the series can be represented in a more general form, which allows us to use the formula for the sum of an infinite geometric series.

    First, let’s rewrite the given series:

    \[
    S = – \frac{2}{3} + \frac{2}{9^2} + \frac{10}{9^3} + \frac{18}{9^4} + \frac{26}{9^5} + \cdots
    \]

    Noticing the pattern in the numerator, we can express the general term of the series as:

    \[
    a_n = \frac{8(n-1) – 6}{9^n}, \quad \text{for } n \geq 2
    \]

    Thus, the series becomes:

    \[
    S = – \frac{2}{3} + \sum_{n=2}^{\infty} \frac{8(n-1) – 6}{9^n}
    \]

    To simplify, we separate the series into two parts: one involving \(8(n-1)/9^n\) and the other involving \(-6/9^n\). This yields:

    \[
    S = – \frac{2}{3} + \left( \sum_{n=2}^{\infty} \frac{8(n-1)}{9^n} \right) – \left( \sum_{n=2}^{\infty} \frac{6}{9^n} \right)
    \]

    The first summation is a geometric series with the first term \(\frac{8}{9^2}\) and common ratio \(\frac{1}{9}\), and the second summation is also a geometric series but with the first term \(\frac{6}{9^2}\) and the same common ratio \(\frac{1}{9}\).

    Using the formula for the sum of an infinite geometric series, \(S = \frac{a}{1 – r}\), where \(a\) is the first term and \(r\) is the common ratio, we calculate the sums of the two series:

    \[
    \sum_{n=2}^{\infty} \frac{8(n-1)}{9^n} = \frac{\frac{8}{9^2}}{1 – \frac{1}{9}} = \frac{8}{72}
    \]

    \[
    \sum_{n=2}^{\infty} \frac{6}{9^n} = \frac{\frac{6}{9^2}}{1 – \frac{1}{9}} = \frac{6}{72}
    \]

    Thus, the sum \(S\) becomes:

    \[
    S = – \frac{2}{3} + \frac{8}{72} – \frac{6}{72}
    \]

    Simplifying further gives:

    \[
    S = – \frac{2}{3} + \frac{1}{9} – \frac{1}{12}
    \]

    Finally, bringing the series to a common denominator and simplifying:

    \[
    S = \frac{-24 + 4 – 3}{36} = \frac{-23}{36}
    \]

    Therefore, the sum of the series is \(\frac{-23}{36}\).

    • This topic was modified 1 month, 2 weeks ago by admin.
    • This topic was modified 1 month, 2 weeks ago by admin.
    • This topic was modified 1 month, 2 weeks ago by admin.
    • This topic was modified 1 month, 2 weeks ago by admin.
    • This topic was modified 1 month, 2 weeks ago by admin.
    • This topic was modified 1 month, 2 weeks ago by admin.
Viewing 1 post (of 1 total)
  • You must be logged in to reply to this topic.